Hubungan Pola Asuh Permissive terhadap Kenakalan Remaja di SMK Muhammadiyah 8 Banyuwangi - Putri, Millenia Zaskia; Ervina, Iin Dwi (Indonesian Journal Publisher, 2023)
Family support is highly important because it can influence the emergence of adolescent delinquency. Parents' monitoring can significantly shape a child's behavior and character as they grow into adulthood. The objective of this study is to explore the relationship between permissive parenting styles and adolescent delinquency at SMK Muhammadiyah 8 Banyuwangi. This research employs a correlational approach with quantitative methods. The study subjects are 10th and 11th-grade adolescents from SMK Muhammadiyah 8 Banyuwangi, with a sample size of 117. The sample was selected using purposive sampling. The scale used to assess adolescent delinquency is a semantic scale with a validity of 0.656 and a reliability of 0.868. The scale for permissive parenting style is a Likert scale with a validity of 0.692 and a reliability of 0.900. Data analysis was conducted using the product moment method. The results of the study indicate a positive correlation between permissive parenting styles and adolescent delinquency at SMK Muhammadiyah 8 Banyuwangi, with a correlation coefficient of 0.553 and a significant level of 0.000. The relative contribution of permissive parenting styles to adolescent delinquency is represented by r² = 0.306, indicating that permissive parenting contributes to 30.6% of the variation, with the remaining influenced by other factors.